The position of the countries of the Greater Horn of Africa in American strategy (Economic studies journal, 2024)
The countries of the Greater Horn of Africa region occupy an important place in American strategic thought, and this has been demonstrated through the strategies and policies adopted by the United States of America in its dealings with the countries of the region, since the end of World War II, from which the United States of America emerged victorious over the Axis countries and its leadership of the Western camp. And it abandoned once and for all the policy of isolation that it had previously adopted. American interest in it did not stop, given the strategic importance that the countries of the region enjoyed, due to several geopolitical, security, geographic, and economic factors, which made it occupy the forefront of the strategic regions that could affect the security and interests of the states. The United States of America, whether during the Cold War period, when the largest scenes of the Cold War took place on its soil, or after it, when the region turned into one of the fronts on which the United States of America implemented its anti-terrorism strategy.”
Keywords: strategy; countries of the Horn of Africa, the United States of America